Microwave group delay equalizers - Brian Wardrop (1970)
A survey of the present state of microwave group-delay equalizers is presented. Based on this, a number of equalizers for use at microwave and millimetric wave frequencies are investigated, both theoretically and experimentally. A microwave group-delay measuring equipment is described, and a comprehensive treatment of possible sources of error presented.